2018
DOI: 10.2139/ssrn.3180638
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Caring for and About Parents and Spouses

Abstract: Informal caregiving is a potentially attractive alternative to formal care but may entail health costs for the caregiver. We examine the mental and physical health impact of providing informal care and disentangle the caregiving effect-the effect of caring for someone in need-from the family effect-the effect of caring about someone in need. We account for the main sources of endogeneity in the caregiving decision using Arellano-Bond difference GMM models. We use four waves (2010-2013) of panel data from the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Considering that the evidence of spillover effects on physical health is relatively rare in the literature compared to the effects on mental health, this finding warrants further research to understand a potential role of mental health deterioration as a mediator for the decline of physical health functioning among caregiving and noncaregiving family members. [42][43][44] Using the 3 different models, we attempted to characterize heterogeneity of the spillover effects according to the age of patients (child/adult) and time of disease occurrence (existing/new). For example, the study conducted by Lavelle et al 45 investigated the variation of spillover effects depending on familial relationship with a patient (e.g., parents, spouse, and child), suggesting that a child patient would induce a greater degree of spillover effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the evidence of spillover effects on physical health is relatively rare in the literature compared to the effects on mental health, this finding warrants further research to understand a potential role of mental health deterioration as a mediator for the decline of physical health functioning among caregiving and noncaregiving family members. [42][43][44] Using the 3 different models, we attempted to characterize heterogeneity of the spillover effects according to the age of patients (child/adult) and time of disease occurrence (existing/new). For example, the study conducted by Lavelle et al 45 investigated the variation of spillover effects depending on familial relationship with a patient (e.g., parents, spouse, and child), suggesting that a child patient would induce a greater degree of spillover effects.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the evidence of spillover effects on physical health is relatively rare in the literature compared to the effects on mental health, this finding warrants further research to understand a potential role of mental health deterioration as a mediator for the decline of physical health functioning among caregiving and noncaregiving family members. 4244…”
Section: Discussionmentioning
confidence: 99%
“…Further, the provision of informal care is known to be psychologically and physiologically challenging (Bom et al, 2019). We examine health outcomes of daughters and sons after a parental stroke.…”
Section: Health Outcomes Of Children After a Parental Strokementioning
confidence: 99%
“…We are interested in the consequences of deteriorating parental health for the labor market outcomes and well-being of adult children. Providing informal care is not only time-consuming, but can also be psychologically and physiologically challenging (Bom et al, 2019). Thus, parents' health may affect their children's allocation of time Schone, 1997, 1999) and their own health.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the support they provide involves substantial time costs and can negatively affect their mental and physical health and well-being [ 5 , 6 ]. Studies have shown that informal caregivers have higher rates of depression, lower levels of well-being, and experience more cardiovascular problems than those not providing informal care [ 7 , 8 , 9 ]. These negative effects can result from the stress caused by trying to meet the competing demands of their family and paid work, social exclusion, and the physically demanding nature of providing care [ 10 ].…”
Section: Introductionmentioning
confidence: 99%